2020
DOI: 10.5578/ced.202002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus, Hepatitis C Virus and Human Immunodeficiency Virus in Children Undergoing Endoscopy in Our Pediatric Gastroenterology Clinic

Abstract: Endoskopi gibi girişimsel işlemler sırasında enfeksiyon bulaşma riski vardır. Bu nedenle, endoskopi ve cerrahi işlemlerden önce enfektif patojenlerin varlığına yönelik rutin testler sağlık çalışanlarının korunması ve hastaların enfeksiyon durumunun belirlenerek danışmanlık, bakım ve tedavi hizmetleri verilmesi yönünden oldukça önemlidir. Bu çalışma, endoskopi yapılan hastaların hepatit B virüsü (HBV), hepatit C virüsü (HCV) ve insan immünyetmezlik virüsü (HIV) enfeksiyonları yönünden değerlendirilmesi ve serop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…In vaccinated children, antibody to hepatitis B surface antigen (anti-HBs) seroprevalence results differ. Today, a level of anti-HBs greater than 10 mIU/ml is regarded as protective (8). Clinical studies have shown that anti-HBs levels decrease as age increases in children vaccinated against hepatitis B (9).…”
Section: Introductionmentioning
confidence: 99%
“…In vaccinated children, antibody to hepatitis B surface antigen (anti-HBs) seroprevalence results differ. Today, a level of anti-HBs greater than 10 mIU/ml is regarded as protective (8). Clinical studies have shown that anti-HBs levels decrease as age increases in children vaccinated against hepatitis B (9).…”
Section: Introductionmentioning
confidence: 99%